PEMANFAATAN MEDIA CANVA DAN APLIKASI QUIZIZZ PADA PEMBELAJARAN TEKS FABEL PESERTA DIDIK SMP - Yesi Maylani Kartiwi; Yeni Rostikawati (STKIP Siliwangi, 2022)
The use of technology in the learning process is an effort to encourage renewal so that the learning process becomes more effective. Utilization of technology in learning can be used in learning media. One of the uses of learning media that uses digital technology is the use of Canva and Quizizz applications. The purpose of this study is to describe the use of learning media assisted by the Canva and Quizizz applications in learning fable texts for junior high school students. The Canva application is a web-based platform that can be used to create various attractive designs. The material for the learning video will be using Canva's design, namely fable text. Meanwhile, Quizizz is a web tool to create interactive quiz games that are used as test assessment tools. The use of Quizizz is expected to make it easier for teachers to carry out assessment tests. This research use desciptive qualitative approach. Based on the research results, Canva and Quizizz applications can be used as online learning media. The use of these two applications makes the learning process not boring, because there are features, templates, designs that can be used to make digital learning media interesting. The use of Canva and the quizizz application is expected to be an alternative for teachers in improving the learning of fable texts for junior high school students.